Recovery from Traumatic Experiences among Children in Conflict-Affected Communities: The Role of Child-Centred Play Therapy and Psychoeducation Interventions - Saleh, Dauda Akwai; Morris, Ruth Emibarsa (NIU Journal of Social Sciences, 2026)
Communities in North Central Nigeria has persistently experience one form of conflict or the other. Children exposed to conflicts are mostly neglected in terms of intervention. The mental health and psycho-social needs of these young survivors are critical, yet there is inadequate data on child-centred evidence-based psychological interventions. This study employed a between-group, pretest-post-test quasi-experimental design to evaluate the effectiveness of a combined Child-Centred Play Therapy and Psychoeducation interventions on trauma-related symptoms among children. The sample consisted of 64 children drawn from selected conflict-affected communities of Bassa and Bokkos local government areas of Plateau state, Nigeria. The participants were equally divided into an intervention group ( n = 32) and a control group ( n = 32). Baseline assessments indicated no statistically significant differences between groups for Post-Traumatic Stress Disorder (PTSD) and Disturbances in Self-Organization (DSO), establishing group comparability. Following the intervention, a Multivariate Analysis of Variance (MANOVA) was conducted at significance level of p = 0.05. The results demonstrated that the intervention had a significant effect on post-test PTSD symptoms, F (1, 62) = 57.139, p < .001, η² = .480, representing a large effect size and a substantial reduction in PTSD symptoms. Similarly, a significant effect was found for post-test DSO, F (1, 62) = 47.481, p < .001, η² = .434. This large effect size indicates that the intervention significantly decreased DSO symptoms among participants. The findings suggest that integrating child-centered play therapy with psycho-education is an effective strategy for reducing trauma-related symptoms in children exposed to conflict affected communities. Keywords: Post-traumatic Stress Disorder, Disturbances in Self-Organization, Mental Health Intervention, Multivariate Analysis of Variance, Nigeria